2018
DOI: 10.1371/journal.pone.0201559
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of surgery for osteophyte-associated dysphagia using the functional outcome swallowing scale

Abstract: PurposeTo investigate the surgical outcome of patients with osteophyte-associated dysphagia (OAD) using the functional outcome swallowing scale (FOSS).MethodsA retrospective chart review of 10 surgical cases of OAD (9 male and 1 female patient; mean age of 65 years) from 1982 to 2017 was performed, and radiographic evaluations were conducted by video fluoroscopic swallow study (VFSS) and conventional radiography. All OAD cases were treated at a single institution, and osteophytes were surgically resected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…Our previous review identified 12 patients with osteophyte recurrence. Currently, we reported 12 patients with recurrent dysphagia, including regrowth of osteophytes in 5 patients, remarkably after a period of 9 years following surgery [99].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous review identified 12 patients with osteophyte recurrence. Currently, we reported 12 patients with recurrent dysphagia, including regrowth of osteophytes in 5 patients, remarkably after a period of 9 years following surgery [99].…”
Section: Discussionmentioning
confidence: 99%
“…A hiperostose crônica parece ser relativamente bem tolerada até que um "evento gatilho", como asfixia, aspiração ou trauma cervical menor, promova um desbalanço na reserva compensatória já limítrofe, levando ao surgimento de um quadro clínico. Múltiplos mecanismos fisiopatológicos têm sido descritos para explicar a sintomatologia relacionada aos osteófitos, como (1) efeito de massa direto, causando obstrução mecânica ou desvio da faringe ou esôfago (2) ; ancoragem do esfíncter esofagiano superior (EES) ao nível da cartilagem cricoide (3) ; restrição ao movimento da laringe ou epiglote (4) ; inflamação do tecido mole subjacente, levando a fibrose e estenose; e (5) neuropatia inflamatória (9) .…”
Section: Discussionunclassified
“…Não existe uma correlação linear entre tamanho do osteófito e sintomatologia, mas se sabe que osteófitos maiores de 10mm aumentam significantemente o risco de aspiração (11) . Uma coorte recente com 10 pacientes portadores de OCA candidatos a tratamento cirúrgico mostrou que metade apresentava perda de peso e desnutrição devido à disfagia, ratificando que o quadro clínico pode ser grave (4) . Foi sugerido um critério de classificação para a intensidade da compressão da parede posterior da faringe.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Although spinal osteophytes are common, occurring in one in every five elderly patients, less than 1% of osteophytes lead to dysphagia. [1][2][3][4][5] This case illustrates how a thorough investigation is essential to evaluate the cause of dysphagia. The patient is currently being managed through a conservative approach due to personal preference.…”
mentioning
confidence: 99%